Kink far below the Fermi level reveals new electron-magnon scattering channel in Fe - E. Młyńczak (Nature Portfolio, 2019)
The conduction electron and magnon interactions are essential for the understanding and development of spintronics and superconductivity. Here the authors show a deep binding energy kink in spin-resolved photoemission spectra which is understood as a signature the many-body spin flip excitation in Fe single crystal thin film.